Fuzzy Database Research group of Simón Bolívar University (Publicaciones en Ciencias y Tecnología, 2018)
This review presents the working trajectory over the last six years of a group of professors from the Department of Computing and Information Technology of the Simón Bolívar University, Caracas, Venezuela, who are focusing their work in the Research of Fuzzy Databases. It includes the background of the group, a historical review, the organization, the achievements in its line of research and the opportunities for growth and continuation in the future.
Keywords: Databases; fuzzy logic; computing and technology; USB; research team; fuzzy